INDONESIAN SOCIETY'S PERCEPTION OF HYPNOTHERAPY COMPARED TO OTHER TYPES OF PSYCHOTHERAPY: A POTENTIAL AND CHALLENGE - Jiemi Ardian (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2022)
Background: Hypnotherapy has demonstrated high efficacy and is recognized for its potential for various clinical or health conditions. However, the perception of hypnotherapy among the general public is very diverse and influenced by many factors, especially compared to other types of psychotherapy. Objective: We aimed to investigate Indonesian society's perception of hypnotherapy compared to other types of psychotherapy. Methods: A cross-sectional survey design was used, targeting users of Twitter and Instagram. The chosen online questionnaires assessed variables, including respondents' characteristic data. This study also used the